THE REPRODUCTIVE AND MARRIAGE BEHAVIOUR OF THE POPULATION OF THE RIVNE REGION - Романів, Оксана; Самчук, Олена (Human Geography Journal, 2015)
The article presents the results of the study of the reproductive and marriage behaviour of the population in the Rivne region. It characterizes the dynamics and territorial differences of the rates of marriage and divorces and defines the coefficient of the stability of families for administrative regions. In addition to that the analysis of the trends of the changes of the main indexes of the reproductive activities of the population is given and is linked to the gender and age structure of the population. As a result there were structural shifts of the reproductive and marriage behaviour elicited; their differences among the regions of the oblast were demonstrated.